Imidazo-anthraquinone derivatives for the chromo-fluorogenic sensing of basic anions and trivalent metal cations - Marín-Hernández, Cristina (2014)
Four imidazo-anthraquinone derivatives (2a-d) functionalized with different aromatic and heteroaromatic groups were synthesized, characterized and their coordination behaviour against selected anions and cations tested. Acetonitrile solutions of probes 2a-d showed charge-transfer absorption bands in the 407-465 nm range whose positions depend on the electron donor strength of the (hetero)aromatic systems appended to the electron-acceptor anthraquinone group. The four probes were also emissive with fluorescence bands in the 533-571 nm interval. The recognition ability of 2a-d was evaluated in the presence of F-, Cl-, Br-, I-, OCN-, BzO-, ClO4-, AcO-, HSO4-, H2PO4- and CN-. Of all anions tested, only F-, AcO- and H2PO4- were able to induce the appearance of new red-shifted absorption bands in the probes that were ascribed to a deprotonation process involving the N-H moiety of the imidazole ring, especially when F- was used. Moreover addition of F-, AcO- and H2PO4- induced moderate quenching in the emission of 2a-d together with the appearance of a new red-shifted emission band. The UV-visible and emission behaviour of the four probes in the presence of Cu2+, Co2+, Mg2+, Fe3+, Ba2+, Fe2+, Ni2+, Ca2+, Zn2+, Pb2+, Cd2+, Cr3+, Al3+, K+ and Li+ was also assessed. Of all cations tested, only addition of the trivalent cations Fe3+, Cr3+ and Al3+ induced the appearance of a new blue-shifted emission in 2a-d that were ascribed to a preferential coordination of these metals with the acceptor part of the probes. Moreover trivalent cations induced an important quenching of the emission for 2a-d.